2020
DOI: 10.21203/rs.3.rs-25715/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

When altruists cannot help: The influence of altruism on mental health during COVID-19 pandemic

Abstract: Background The positive predictive effect of altruism on physical and psychological well-being has been extensively demonstrated in previous studies, but few studies have examined the effect of altruism on negative mental health outcomes when altruists cannot perform altruistic behaviors. This study explored the influence of altruism on negative affect and mental health (anxiety and depression) during the outbreak of the COVID-19 pandemic, when people self-isolated at home in China.Method: College students wer… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
14

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 0 publications
1
8
0
14
Order By: Relevance
“…This study examined the effects of risk perception of COVID-19 on psychological disorders and found that increased psychological disorders was produced by higher risk perception of COVID-19. These results supported the ndings of previous studies [35]. The negative impact caused by the ampli cation of risk perception of COVID-19 exceeded the direct impact of COVID-19 itself [36].…”
Section: Discussionsupporting
confidence: 91%
“…This study examined the effects of risk perception of COVID-19 on psychological disorders and found that increased psychological disorders was produced by higher risk perception of COVID-19. These results supported the ndings of previous studies [35]. The negative impact caused by the ampli cation of risk perception of COVID-19 exceeded the direct impact of COVID-19 itself [36].…”
Section: Discussionsupporting
confidence: 91%
“…1. Finally, this meta-analysis included 84 studies with a total of 1 292 811 Chinese university students (Cao, 2020; Chang et al ., 2020; Chen et al ., 2020 a , 2020 b , 2020 c , 2020 d ; Chi et al ., 2020; Cong et al ., 2020; Deng et al ., 2020; Dong, 2020; Dong et al ., 2020; Feng, 2020; Feng et al ., 2020; Han et al ., 2020; Ji et al ., 2020; Jiang et al ., 2020; Lei et al ., 2020; Li and He, 2020; Li et al ., 2020 b ; Lian et al ., 2020; Liang et al ., 2020 a , 2020 b ; Lin and Xu, 2020; Lin et al ., 2020 a , 2020 b ; Liu, 2020 a , 2020 b ; Liu et al ., 2020 a , 2020 b , 2020 c ; Ma et al ., 2020 a , 2020 b ; Mao et al ., 2020; Qian, 2020; Ren et al ., 2020 a , 2020 b ; 2020 c ; Si et al ., 2020; Sun et al ., 2020, 2021; Tang et al ., 2020; Wan and Shao, 2020; Wang and He, 2020; Wang and Li, 2020; Wang et al ., 2020 b ; 2020 c ; 2020 d ; 2020 e ; 2020 f ; 2021; Wei, 2020; Wu et al ., 2020, 2021; Xiang et al ., 2020; Xiao et al ., 2020 a , 2020 b ; Xie et al ., 2020; Xin et al ., 2020; Xing et al ., 2020; Xiong et al ., 2020; Xu and Li, 2020; Yan et al ., 2020; Yang et al ., 2020 b ; Yao et al ., 2020; Yi et al ., 2020 a , 2020 b ; Yu et al ., 2020, 2021; Zhan et al ., 2020; Zhang et al ., 2020 b , 2020 c , 2020 d ,…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we assume that the causes of these problems might be social isolation, the surrounding risks and uncertainties, pain and suffering, drug reactions, worrying about spreading the contagion to others, and negative information consumed on social networks [ 12 ]. Studies have investigated the first wave of the pandemic and observed mental health problems such as PTSS/PTSD, anxiety, and depressive symptoms among health care workers or the general population [ 13 16 ]. Few studies have investigated mental health problems among patients infected by COVID-19 during the second wave.…”
Section: Introductionmentioning
confidence: 99%